2020
DOI: 10.1155/2020/8858291
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Wound Healing and Anti‐Inflammatory Activities of Babassu Oil (Attalea speciosa Mart. Ex Spreng., Arecaceae)

Abstract: Babassu (Attalea speciosa Mart. ex Spreng., Arecaceae) is a palm tree endemic to Brazil and found mainly in the borders of Amazon forest, where the harvesting of its fruits is an important source of income for more than 300,000 people. Among the communities of coconut breakers women, babassu oil is used in culinary, as fuel, and mostly as medicinal oil for the treatment of skin wounds and inflammation. This study aimed to evaluate in vitro and in vivo the wound healing effects of babassu oil. In vitro, babassu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…The molecular docking experiment indicated that naringenin could bind tightly to these screened key target proteins. The endotoxin lipopolysaccharide (LPS) is a component of gram-negative bacteria and is widely used to simulate the inflammatory and oxidative stress state of wound healing in vitro 89 , 109 , 110 . LPS binds to Toll-like receptor 4 (TLR4) and activates multiple signalling pathways through signal transduction, including NF-κB p65/RELA and MAPKs, ultimately resulting in increased transcription of the proinflammatory cytokines TNF-α and IL-6 111 .…”
Section: Discussionmentioning
confidence: 99%
“…The molecular docking experiment indicated that naringenin could bind tightly to these screened key target proteins. The endotoxin lipopolysaccharide (LPS) is a component of gram-negative bacteria and is widely used to simulate the inflammatory and oxidative stress state of wound healing in vitro 89 , 109 , 110 . LPS binds to Toll-like receptor 4 (TLR4) and activates multiple signalling pathways through signal transduction, including NF-κB p65/RELA and MAPKs, ultimately resulting in increased transcription of the proinflammatory cytokines TNF-α and IL-6 111 .…”
Section: Discussionmentioning
confidence: 99%
“…Babassu oil is rich in lauric acid, myristic acid, and oleic acid (Table 2) [89]. Lauric fats are very important in industry, as they are resistant to non-enzymatic oxidation and, unlike other saturated fats, they have a low and well-defined melting temperature [104].…”
Section: Amazonian Oil and Their Use In The Formation Of Organogelsmentioning
confidence: 99%
“…The splinted full thickness model was used study the effects of recombinant myxoma virus-derived immune modulator M-T7 [49], of Babassu oil [50], of three-dimensional printed scaffolds and electrospun mats [51], of adult gingival multipotent mensenchymal stem cells [52], of induced pluripotent stem cells clay [53], of poly(lactic-co-glycolic acid) and vascular endothelial growth factor [54], and of renal dysfunction [44] on cutaneous wound healing.…”
Section: The Splinted Full Thickness Modelmentioning
confidence: 99%